On the third depth distribution and the period of sequence {（E-1）～m（s）}m≥0 over F2 - ZENG Min1～3; LUO Yuan1 (Tongxin xuebao)
The complexity of a vector can be investigated in terms of three kinds of depths,which were introduced by Etzion and Roth. The third depth distribution of F2 n was provided according to the relationship of period and the third depth of finite sequences. Then the ultimate period of sequence {（E-1）m（s）}m≥0 was considered,when the third depth of the vector s is ∞.